Where to Spend the Next Million? Applying Impact Evaluation to Trade Assistance - Cadot, Olivier; Fernandes, Ana M.; Gourdon, Julien; Mattoo, Aaditya (London: Centre for Economic Policy Research and the World Bank, 2013)
Trade policy has changed fundamentally since the days of structural adjustment and economy-wide trade reforms. Partly in reaction to the uneven results of trade policy reforms, the focus has shifted to more targeted interventions aimed at reducing trade costs and addressing market failures that inhibit exports. Significant national resources and international assistance are now devoted to trade facilitation and export promotion, and the international development community has galvanized around a new 'aid-for-trade' (AfT) mantra as a means of helping low-income countries integrate into the global economy. The rest of this chapter is organized as follows: in section two the report discusses the changing nature of trade policy. In section three the report reviews the available evidence on the impact of trade assistance. In section four the report considers a detailed menu of trade-related interventions and discusses the challenges to their evaluation. In section five the report addresses the data issues crucial to impact evaluation. Finally, in section six the report look at the future challenges to doing Independent Evaluation (IE) in trade assistance.